The Mind Mapping Learning Model on Student Learning Outcomes Subtema 2 Togetherness in Diversity Class IV UPTD SD 122365 Pematang Siantar - Lira Anacarelina Siregar; Lisbet novianti Sihombing; Natalina Purba (International Journal of Integrated Science and Technology, 2023)
This study aims to determine the influence of the mind mapping learning model on student learning outcomes, subtheme 2, togetherness in diversity, class iv uptd sd 122365 pematang siantar. The method in this research is a quantitative experimental type method whose research design is pre-experimental, one group pretest-posttest type. The population and sample used was saturated sampling with a sample of 23 people with two research variables: the dependent variable (x) in the form of learning outcomes, and the independent variable (y) in the form of mind mapping learning . The data collection technique is the test technique. Test results using the T-test with the help of the SPSS version 21 program, based on calculation results obtained tcount = 23.182 with a significance level (2-tailed) 0.000, significant probability < 0.005, tcount> ttable = 23.182 > 2.069 then H o is rejected and Ha a is accepted. This explanation shows that there is an influence of the Mind Mapping Learning Model on the Learning Outcomes of Class IV Students, Subtheme 2, Togetherness in Diversity, SD Negeri 122365 Pematang Siantar.